Designing and pilot testing a novel high-definition transcranial burst electrostimulation device for neurorehabilitation. (17th September 2021) - Wang, Shun-Min Samuel; Huang, Yi-Jing; Chen, Jia-Jin Jason; Wu, Chun-Wei; Chen, Chien-An; Lin, Che-Wei; Nguyen, Van-Truong; Peng, Chih-Wei
Abstract: Objective. Non-invasive brain stimulation has been promoted to facilitate neuromodulation in treating neurological diseases. Recently, high-definition (HD) transcranial electrical stimulation and a novel electrical waveform combining a direct current (DC) and theta burst stimulation (TBS)-like protocol were proposed and demonstrated high potential to enhance neuroplastic effects in a more-efficient manner. In this study, we designed a novel HD transcranial burst electrostimulation device and to preliminarily examined its therapeutic potential in neurorehabilitation. Approach. A prototype of the transcranial burst electrostimulation device was developed, which can flexibly output a waveform that combined a DC and TBS-like protocol and can equally distribute the current into 4 × 1 HD electrical stimulation by automatic impedance adjustments. The safety and accuracy of the device were then validated in a series of in vitro experiments. Finally, a pilot clinical trial was conducted to assess its clinical safety and therapeutic potential on upper-extremity rehabilitation in six patients with chronic stroke, where patients received either active or sham HD transcranial burst electrostimulation combined with occupational therapy three times per week for four weeks. Main results. The prototype was tested, and it was found to comply with all safety requirements. The output parameters were accurate and met the clinical study needs. The pilot clinical study demonstrated that the active HD transcranial burst electrostimulation group had greater improvement in voluntary motor function and coordination of the upper extremity than the sham control group. Additionally, no severe adverse events were noted, but slight skin redness under the stimulus electrode immediately after stimulation was seen. Conclusions. The results demonstrated the feasibility of incorporating the HD electrical DC and TBS-like protocol in our device; and the novel neuromodulatory device produced positive neurorehabilitation outcomes in a safe fashion, which could be the basis for the future clinical implementation for treating neurological diseases. Trial registration: ClinicalTrials.gov Identifier: NCT04278105. Registered on 20 February 2020.